Factors associated with non-adherence to antidiabetic medication: a single-centre study in South Punjab, Pakistan - Allahdad Khan; Ashfaq, Urwa; Aziz, Beshair; Malik, Rohma; Jamil, Muhammad Farhan; Saleem, Umera (Journal of the Pakistan Medical Association, 2026)
Objective: To identify and evaluate key barriers to medication adherence among diabetes mellitus patients. Method: The descriptive, cross-sectional study was conducted at Nishtar Hospital, Multan, Pakistan, from November 5 to December 10, 2024, and comprised diabetic inpatients aged at least 20 years. Data was collected using a predesigned questionnaire based on the Hill Bone Medication Adherence Scale. Data was analysed using SPSS 23. Results: Of the 176 patients with mean age 51+-8.6 years (range: 22-73 years), 92(52.3%) were females and 84(47.7%) were males. Factors having a significant association with non-adherence to anti-diabetes medication were age >60 years, monthly salary >50,000 Pak rupee, family history of diabetes, multiple doses, duration of diabetes 5 years or more, and education level beyond high school (p<0.05). Gender and the route of administration had no significant association with non-adherence (p>0.05). Conclusion: Diabetic patients with higher income, family history and education were found to have better medication adherence, while advanced age and multiple doses decreased adherence. Key Words: Patient compliance, Medication adherence, Diabetes mellitus, Pakistan, Hypoglycaemic agents.